Poland and global value chains at the beginning of the 21st century: An opportunity or a threat? - Aleksandra Nacewska-Twardowska (International Journal of Management and Economics, 2022)
This article aims to examine and present trade relations in global value chains (GVCs) and their impact on Polish trade, emphasizing Poland's ability to react to rapid changes in the global economy, as in the case of the COVID-19 pandemic. For this purpose, the author proposed a two-stage study. The first stage focuses on analyzing selected indexes describing the Polish share and position in GVCs against the background of the European Union (EU) and OECD countries. The second stage is related to the analysis of the latest economic trade data and the reaction of Poland, the EU, and OECD to changes in international trade in 2020 and 2021 in the context of GVC. The study uses data from the OECD and WTO Trade in Value Added Database and the Eurostat Database. The relatively quick adaptation of Poland to the world's standards indicates great possibilities for adaptation of the Polish economy. The share of foreign value added in Polish exports was consistent with global trends. The export orientation of Polish production increased during the analyzed period, proving Poland's deep commitment to global production chains. Despite a similar decline in import and export in the first months of 2020, as in the OECD and the EU26, the growth dynamics in the following months were higher in Poland. Many industries in Poland are highly dependent on the smooth operation of GVCs. At the same time, the service sector is gaining importance, and its share in exports is systematically growing. The highly flexible nature of Poland's international trade allowed it to reduce the negative impact of the COVID-19 pandemic on its economy.
Keywords: F13; F15; F6; 650; global value chain; GVC; GVC participation; GVC position; trade